Variation of Energy in Photobiomodulation for the Control of Radiotherapy-Induced Oral Mucositis: A Clinical Study in Head and Neck Cancer Patients - Cizelene do Carmo Faleiros Veloso Guedes; Silas Antonio Juvencio de Freitas Filho; Paulo Rogério de Faria; Adriano Mota Loyola; Robinson Sabino-Silva; Sérgio Vitorino Cardoso (International Journal of Dentistry)
Oral mucositis (OM) is a frequent and severe adverse effect of therapy against head and neck cancer. Photobiomodulation with the low-power laser is known to be effective against OM, but the diversity of protocols and the possibility of stimulating residual tumor cells are still obstacles. The present study aimed to compare two doses of laser energy delivered to the oral mucosa of patients under oncologic treatment for head and neck cancer, looking for differences in the control of mucositis, as well as in the frequency of tumoral recurrences. Fifty-eight patients undergoing radiotherapy were randomized into two groups, distinguished according to the energy delivered by laser irradiation, namely, 0.25 J and 1.0 J. The groups were compared according to frequency, severity, or duration of OM, as well as the frequency of tumoral recurrences. OM was significantly less frequent in patients receiving 1.0 J of energy, but the groups did not differ regarding severity or duration of OM. Tumoral recurrence also did not vary significantly between the groups. Photobiomodulation with a higher dose of energy (1.0 J versus 0.25 J) is associated with better control of radiotherapy-induced OM and does not significantly increase the risk of neoplastic recurrence.